Sensitivity Analysis and Parameter Optimization for the Fractionative Catalytic Conversion of Lignocellulosic Biomass in the Polyoxometalate-lonosolv Concept - Bukowski, Anna; Schnepf, Kristin; Wesinger, Stefanie; Brandt-Talbot, Agnieszka; Albert, Jakob (ACS Sustainable Chemistry & Engineering, 2022)
The recently developed polyoxometalate (POM)-ionosolv concept offers an interesting strategy to generate two valuable product streams from lignocellulosic biomass, a solid cellulose-rich pulp and short-chain carboxylic acids like formic acid and acetic acid in a simple and cost-efficient manner. This study aimed to find optimum parameters for the two steps of the transformation by performing a sensitivity analysis on the initial ionosolv fractionation step as well as kinetic investigations of the following POM-catalyzed oxidation step. The results were transferred to the POM-ionosolv concept to find the overall process optimum. Beech wood was used as an industrially relevant substrate for ionosolv fractionation with the low-cost ionic liquid triethylammonium sulfate, [TEA][HSO4], and the HPA-5 [H8PV5Mo7O40] POM catalyst for the oxidation of the dissolved components in an oxygen atmosphere. As the most seminal finding, we defined optimum conditions of 125 degrees C, 1200 rpm, 30 bar oxygen, and 24 h reaction time in ionic liquid containing 70% water, achieving 72% xylose extraction from beech wood, which resulted in a 39% formic acid yield. We suggest that the fractionation and catalytic conversion are carried out at different water contents for maximum conversion efficiency for each step.
CRIS-Team WoS Importer:2022-07-08
Keywords: Lignocellulose; Fractionation; Ionic liquid; Polyoxometalate; Formic acid; Cellulose